For the Fatherland? The Motivations of Austrian and Prussian Volunteers during the Revolutionary and Napoleonic Wars - Leighton James (War Volunteering in Modern Times: From the French Revolution to the Second World War, 2011)
This book chapter examines the motivation for military service in Revolutionary and Napoleonic Wars in German Central Europe. The chapter argues that contrary to nineteenth-century interpretations of the German and Austrian war effort, patriotism and nationalism were relatively weak factors underpinning the decision to enlist. It was usually more pragmatic concerns, such as subsistence, career advancement or the allure of military life, that often led men to volunteer for the army. This applied even to the German volunteers of the Wars of Liberation (1813-1815), who were subsequently lionized as forerunners of German nationalism.